Effects of histone hyperacetylation on the preimplantation development of male and female bovine embryos - Oliveira, Clara S. [UNESP]; Saraiva, Naiara Z. [UNESP]; de Souza, Marcela M. [UNESP]; Tetzner, Tatiane A. D. [UNESP]; de Lima, Marina R. [UNESP]; Garcia, Joaquim Mansano [UNESP] (CSIRO Publishing, 2010)
Trichostatin A (TSA) induces histone hyperacetylation by inhibiting histone deacetylases and consequently increasing gene expression. The hypothesis was that TSA supplementation during the in vitro culture (IVC) of bovine embryos would increase the blastocyst rate, particularly in low-quality and female embryos. Oocytes were fertilised separately with X and Y spermatozoa and, 70 h after IVF, the IVC medium was supplemented with 5 nM and 15 nM TSA for 48 or 144 h. Incubation of female embryos with 5 nM and 15 nM TSA resulted in similar increases in acetylated histone H3K9 levels. However, to see comparable effects on acetylated histone H3K9 levels in male embryos, the culture medium needed to be supplemented with 15 nM TSA (as opposed to 5 nM TSA for female embryos). Treatment of male and female embryos with 5 nM TSA for 48 h or female embryos with 5 nM for 144 h had no effect on blastocyst rates, although 15 nM TSA compromised embryonic development. The terminal deoxyribonucleotidyl transferase-mediated dUTP-digoxigenin nick end-labelling (TUNEL) assay revealed increased apoptosis in female embryos treated with 5 nM TSA for 144 h, as well as in male and female embryos treated with 15 nM TSA for 48 h, but this increase in apoptosis was not observed in low-quality embryos. The results of the present study suggest that TSA treatment promotes histone hyperacetylation, but has no beneficial effects on the in vitro production of male and female bovine embryos during preimplantation development.
Keywords: Epigenetics; histone deacetylase inhibition; histone H3 lys9 acetylation; immunocytochemistry; trichostatin A; TUNEL assay